Multilateral political effects on outbound tourism - Bo Zhou; Ying Zhang; Peng Zhou (Cardiff University, Cardiff Business School, 2021)
To capture the role of politics in tourism, we propose a novel measure to quantify political relations based on text analysis of published diplomatic statements. We explain how political relations affect outbound tourist flows from China to Japan and Korea. Estimated on monthly data (1997m1-2018m12), our model shows how China-Japan disputes affect tourist flows to Korea and how China-Korea clashes influence the number of Chinese tourists going to Japan. The political effects are estimated to peak after three months, but half of the effects vanish in six months. We also observe asymmetries in the political effects - the tourists respond more to negative political shocks than to positive ones, and more to territorial disputes than to war history disputes.
Keywords: 330; political relation; outbound tourism; China; multilateral interdependence